Deference the legal concept and the legal practice - Lawson, Gary 1958-; Seidman, Guy (Oxford University Press, 2020)
"This is a descriptive account of the concept and practice of deference in the law, with the goal of providing a definition and analytical framework that can be applied to all of the many forms of deference that appear in any legal system. Deference is central to almost everything that happens in law but has not been the subject of systematic study, perhaps because it shows up in so many different forms and places. We hope to provide a definition and vocabulary for the study of deference that anyone, from any perspective, can use"--
Includes bibliographical references and index
Keywords: Ehrerbietung; USA; Deference (Law) / United States; Law / United States / Interpretation and construction; Judicial review / United States